Tracheal remodelling in response to hypoxia - Centanin, L. (2010)
The insect tracheal system is a continuous tubular network that ramifies into progressively thinner branches to provide air directly to every organ and tissue throughout the body. During embryogenesis the basic architecture of the tracheal system develops in a stereotypical and genetically controlled manner. Later, in larval stages, the tracheal system becomes plastic, and adapts to particular oxygen needs of the different tissues of the body. Oxygen sensing is mediated by specific prolyl-4-hydroxylases that regulate protein stability of the alpha subunit of oxygen-responsive transcription factors from the HIF family. Tracheal cells are exquisitely sensitive to oxygen levels, modulating the expression of hypoxia-inducible proteins that mediate sprouting of tracheal branches in direction to oxygen-deprived tissues. © 2009 Elsevier Ltd. All rights reserved.